Abundance and biomass of Bdelloid rotifers in the microbial mats from East Antarctica: The ecological relations between microscopic phototrophs and invertebrates. Issue 2 (30th November 2022) - Wada, Tomotake; Kudoh, Sakae; Koyama, Hiroshi; Iakovenko, Nataliia; Elster, Josef; Kvíderová, Jana; Otani, Masahiro; Shimada, Sho; Imura, Satoshi
Abstract: Microbial mats in Antarctica are known to harbor microscopic organisms. Recently, comprehensive studies of the diversity of microbial mats have been conducted using genetic analysis of 16 S rRNA and 18 S rRNA genes. However, the quantitative biological contribution of each microorganism constituting the microbial mats remains unknown. We surveyed microscopic phototrophs and invertebrates in mats sampled from five lakes and one ephemeral wetland on the Sôya Coast, East Antarctica. We identified seven taxonomic groups of phototrophs, of which five (Orders Chroococcales, Nostocales, and Oscillatoriales, and Classes Chlorophyceae and Bacillariophyceae) were found at all sites, and three taxonomic groups of invertebrates (Class Bdelloidea, and Phyla Nematoda, Tardigrada). Bdelloidea were the most predominant invertebrate group at all sampling sites. The biomass of the Bdelloidea was 4–10 times higher than the total biomass of the Nematoda and Tardigrada at all sampling sites. The total biomass of all groups identified was higher in the ephemeral wetland than in the lakes. Of the five lakes, Skallen Ôike had the highest total biomass. These findings suggest that higher biomasses exist in eutrophic environments (the marine relict lake, Skallen Ôike, and an ephemeral wetland) where nutritional carryover or higher nutritional flux is expected. In addition, statistical differences in the community structure among the lakes and the ephemeral wetland could be detected based on the biomass compositions of the taxonomic groups. The community structure of each lake and the wetland was statistically dissimilar, indicating the phototrophs and invertebrates had a unique community structure at each study site. Abstract : We surveyed microscopic phototrophs and invertebrates in mats sampled from five lakes and one ephemeral wetland on the Sôya Coast, East Antarctica. Bdelloidea were the most predominant invertebrate group at all sampling sites. The community structure of each lake and the wetland was statistically dissimilar, indicating the microscopic phototrophs and invertebrates had a unique community structure at each study site.